Un cercueil dans la cour : des funérailles évangéliques dans une famille transnationale haïtienne - Nadège Mézié (Journal de la Société des Américanistes, 2021)
While Haitian vodou funerals have been studied extensively by anthropologists, little is known about how they are organized and carried out by evangelical families and churches. This article offers a detailed case study of an evangelical funeral in the mountains of southwestern Haiti, in a family with many members of the diaspora. The first part details the ritual, from the treatment of the corpse to the burial service. The second part offers an analysis of the funerals, and in particular the conflicts that have arised as a result of two broader social dynamics: the religious change in the country, with the massive conversion of rural populations to Evangelical and Pentecostal Protestantism, and the migrations, which fled to most Haitian families having at least one member living abroad.